The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5194/hess-2017-98
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Responses of runoff to historical and future climate variability over China

Abstract: China has suffered some of the effects of global warming, and one of the potential implications of climate warming is the 10 alteration of the temporal-spatial patterns of water resources. Based on the long-term water budget data and climate projections from 28 Global Climate Models (GCMs) of the Coupled Model Intercomparison Project Phase 5 (CMIP5), this study investigated the responses of runoff (R) to historical and future climate variability in China at both grid and catchment scales using the Budyko-base… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The Mann-Kendall (M-K) test is a non-parametric statistical method for testing the trend of hydrometeorological data ( Dawood 2017;Kendall 1975;Mann 1945). The M-K method has the advantages of not assuming any distribution forms for the data and not being affected by interference from outliers, and is widely used for detecting the significance of long-term trends in hydrometeorological variables (Gocic and Trajkovic 2013;Li et al 2021;Mekonen and Berlie 2020;Wu et al 2018). In this study, we apply the M-K method to detect the statistical significance of the trends in FD characteristics (D, I and P) at the 5% significance level (a = 0.05).…”
Section: Mann-kendall Trend Testmentioning
confidence: 99%
“…The Mann-Kendall (M-K) test is a non-parametric statistical method for testing the trend of hydrometeorological data ( Dawood 2017;Kendall 1975;Mann 1945). The M-K method has the advantages of not assuming any distribution forms for the data and not being affected by interference from outliers, and is widely used for detecting the significance of long-term trends in hydrometeorological variables (Gocic and Trajkovic 2013;Li et al 2021;Mekonen and Berlie 2020;Wu et al 2018). In this study, we apply the M-K method to detect the statistical significance of the trends in FD characteristics (D, I and P) at the 5% significance level (a = 0.05).…”
Section: Mann-kendall Trend Testmentioning
confidence: 99%
“…Numerous studies have evaluated regional hydrological response to future climate change by combination of hydrological models and scenarios based on climate model outputs (Masood et al, 2015;Wang, Zhang, Jin, et al, 2012;Wu et al, 2018;Zhang, Fu, et al, 2015). For example, Wang, Zhang, Jin, et al (2012) found that the annual runoff of China from 2021 to 2050 would probably increase 3%-10% compared with 1961-1990 by VIC model.…”
mentioning
confidence: 99%